Information psychological factors the impact of visual advertising on consumer - Vainshtein, Lev A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The analysis of the main areas of advertising. Highlighted two main traditions in advertising. The first (German) based on the experimental psychological work of studying laws of information processing. The second (American) is based on the ideas of marketing and is based on the needs of the people. Shows the development of these traditions in the present and the trends towards convergence. The role of various psychological factors of the influence of visual information on consumers based on: attention, perception, memory, thinking, beliefs, needs, actions, attitude, and decision-making. The analysis of basic information models the visual impact of the information on the person: AIDА, AIMDA, ACCA, DIBABA, DAGMAR, attitude, basis of reference. Described the mental processes of the influence of advertising exposure on the consumer. Set out a comparative analysis of the effectiveness of various information models used in advertising.